From the Farmstead to the Condo:: Douglas Fetherling on Literature and Publishing in Canada - Ball, John (Studies in Canadian Literature / Études en littérature canadienne, 2000)
Douglas Fetherling, the poet, writer and editor, began his literary life working for the fabled House of Anansi Press in the late 1960s. He speaks about the changing literary environment, noting that it has grown much more complex and cosmopolitan than when he started at Anansi in the 1960s. Fetherling discusses changes in book design and editorial work, and argues that ownership is crucial in the Canadian publishing industry. He outlines the rise of the literary agent in the 1990s and comments on the decline of independent bookselling. He notes that the Canadian canon has expanded over the years with the advent of disciplines such as gender studies, Native studies, postcolonial studies and the subsuming of literature into cultural studies, pointing out the fragility of Canadian literature.